Boreal and tundra microclimates : New insights from in situ measurements and process-based modelling - Tyystjärvi, Vilna (Helsingin yliopisto, 2024)
In high-latitude regions, climate change is advancing notably faster than the global average and changes in the local environments are already occurring. However, large uncertainties still exist concerning how the climate at fine spatial scales, i.e. the microclimate, responds and feeds back to the large-scale climate, i.e. the macroclimate. Microclimates refer to conditions near or within the land surface, which can deviate considerably from ambient atmospheric conditions due to land surface properties such as vegetation cover and topography. Since microclimates are controlled by local environmental conditions, studying their role in different landscapes is crucial for a better understanding of how microclimates function now and how they might change in the future. Some microclimates may, under certain conditions, change more slowly than macroclimates, which in turn may locally hinder climate change and its environmental impacts. On the other hand, some changes, such as the disappearance of snow cover in northern ecosystems, may drastically alter microclimates and amplify the effects of climate change. In this thesis, I investigate the temporal and spatial variability of microclimates and their environmental drivers in boreal and tundra landscapes, utilising both empirical and process-based approaches. The first chapter focuses on fine-scale soil moisture dynamics in mountain tundra by comparing in situ measurements and simulations of two process-based models. In the second and third chapters, I investigate the magnitude and drivers of microclimate temperatures through an extensive measurement campaign covering seven landscapes in Finland. In the second chapter, the focus is on vertical and spatial variability as well as seasonal differences, while in the third chapter, I study fine-scale variability in seasonal snow cover duration and its impact on near-surface temperatures. Finally, in the fourth chapter, I use process-based modelling to understand the impacts of climate change and forest management practices ...